Enhancement of Hydrophobicity of Fish Skin Gelatin via Molecular Modification with Oxidized Linoleic Acid - Wipawee Theerawitayaart; Thummanoon Prodpran; Soottawat Benjakul (Journal of Chemistry)
Fish gelatin possesses hydrophilicity in nature since it contains a few hydrophobic amino acids and a large portion of hydrophilic amino acids. Low hydrophobicity of fish gelatin results in poor water vapor barrier and water resistance of gelatin films. This can limit its usage as packaging material. To overcome this drawback, the molecular attachment of hydrophobic domains can effectively improve the hydrophobicity of fish gelatin. In this study, fish skin gelatin modified with oxidized linoleic acid (OLA) prepared under various conditions using different molar ratios of OLA/free amino group content was characterized. When OLA was prepared at 60 and 80°C for various oxidation times (0–24 h), the peroxide value (PV) increased continuously up to 9 and 12 h when reaction was performed at 80 and 60°C, respectively. Consequently, the PV decreased until the end of the reaction (24 h). Thiobarbituric acid reactive substances (TBARS) of OLA were increased sharply up to 12 h, regardless of reaction temperatures. Thus, primary and secondary lipid oxidation products mainly occurred within the first 12 h. As gelatin was modified with different OLA at various OLA/free amino group molar ratios, the one modified with OLA prepared at 60°C for 24 h at a molar ratio of 10 : 1 had the highest increases in surface hydrophobicity and carbonyl content with the coincidentally lowest free amino group content, compared with control gelatin (without OLA modification). Fourier transforms infrared (FTIR) spectra also reconfirmed the presence of fatty acid covalently attached to resulting gelatin. Therefore, OLA could be used to modify gelatin and increase its hydrophobicity.